Intimate Encounters: Screendance and Surveillance - John White (The International Journal of Screendance, 2017)
This article explores some ways in which screendance might invite a greater or deeper degree of kinesthetic empathy than is traditionally possible with live performance. In particular, the use of the close-up and the creation of editing rhythms are two strategies that extend screendance viewers' kinesthetic empathy into a more intimate relationship with the dance(rs). Furthermore, this article analyzes Katrina McPherson's screendance The Truth as a case study in which this intimate viewing relationship is characterized by a kind of voyeurism shared with the act of viewing surveillance. I draw on some surveillance theory and artist Jill Magid's piece Evidence Locker in order to explore the surveillance aspects of The Truth.